2010
DOI: 10.1111/j.1096-3642.2009.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of the pygmy rice rats of the genus Oligoryzomys Bangs, 1900 (Rodentia: Sigmodontinae)

Abstract: Sequences from two mitochondrial genes (cytochrome b and NADH1) were used to produce a molecular phylogeny for 12 named and two undescribed species of the genus Oligoryzomys. All analyses placed Oligoryzomys microtis as the most basal taxon, a finding consistent with previous studies that suggested the west-central Amazon as a centre of origin for the tribe Oryzomyini to which Oligoryzomys belongs. Biogeographically, this suggests that Oligoryzomys had a South American origin, and later advanced northwards, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 55 publications
1
41
1
2
Order By: Relevance
“…8). Some clades recovered in the present study, both in the mt-Cytb only and in combined analyses, are generally coincident with recent studies of Oligoryzomys (Palma et al, , 2010aFrancés and D'Elía, 2006;Rivera et al, 2007;Rogers et al, 2009;Miranda et al, 2009;Richter et al, 2010;González-Ittig et al, 2010 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…8). Some clades recovered in the present study, both in the mt-Cytb only and in combined analyses, are generally coincident with recent studies of Oligoryzomys (Palma et al, , 2010aFrancés and D'Elía, 2006;Rivera et al, 2007;Rogers et al, 2009;Miranda et al, 2009;Richter et al, 2010;González-Ittig et al, 2010 …”
Section: Discussionsupporting
confidence: 71%
“…Recent phylogenetic studies of this genus (Rivera et al, 2007;Rogers et al, 2009;Miranda et al, 2009;Palma et al, 2010a;González-Ittig et al, 2010Hanson et al, 2011;Agrellos et al, 2012;Teta et al, 2013) have shown that Oligoryzomys systematics is still controversial, probably due to the high phenotypic similarity between species, which makes diagnosis and species identification difficult (see Musser, 1989, 1995;Weksler andBonvicino, 2005, 2015, for historical accounts of the generic taxonomy). In addition, molecular studies not employing morphological examination of specimens hinders further advance of the systematics of the genus, as specific names have been attached to several exemplars without a proper morphological assessment or that are based solely on geographic proximity of species ranges or type localities.…”
Section: Introductionmentioning
confidence: 99%
“…Although in general, each hantavirus is associated with a single primary host species, several apparent exceptions to this pattern in the Southern Cone may relate to our imperfect knowledge of the taxonomy of the host species. Recent work on the phylogenetics of Oligoryzomys Gonzalez-Ittig et al, 2010;Palma et al, 2010) has contributed to our understanding of the complexity of the relationships between species of Oligoryzomys and several hantaviruses. We now know, for example, that the host for Oran virus is Oligoryzomys chacoensis, not Oligoryzomys longicaudatus (host for ANDV), as originally described .…”
Section: Host-virus Associationsmentioning
confidence: 99%
“…Nevertheless, the complex and still relatively poorly understood systematics of many sigmodontine rodents in South America, combined with the scant sampling records for some taxa, complicate the documentation of accurate distributional data. Although several species once believed to be distributed across large geographic areas (e.g., O. longicaudatus and O. flavescens) are being recognized as complexes of species or subspecies Palma et al, 2010;Gonzalez-Ittig et al, 2010), other widespread species (e.g., C. laucha) are still in need of careful taxonomic study.…”
Section: Geographic Distributions Of Hosts and Virusesmentioning
confidence: 99%
“…5 to 10 % [Feijoo et al 2010;D'Elía et al in press]; species of the Akodon boliviensis species group: 2.8-7.7 % [Jayat et al 2010]; Eligmodontia: 4.6-11.4 % [Mares et al 2008]; Juliomys: ca. 12 % ; Melanomys: 4.5-7.6 % [Hanson and Bradley 2008]; Nectomys: 7.36 % [Hanson and Bradley 2008]; Oligoryzomys: 4.45-15 % [Hanson et al 2011;Palma et al 2010;Richter et al 2010;Rogers et al 2009]; Oryzomys: 4.5-12.1 % ; Oxymycterus: 2.5-9.6 % [Jayat et al 2008 [Henson and Bradley 2009]). Although the species used for comparison are not the closest possible relatives to Neusticomys, all belong to other sigmodontine tribes and provide a diverse array of reference points.…”
Section: Discussionmentioning
confidence: 99%